2011
DOI: 10.1051/bioconf/20110100004
|View full text |Cite
|
Sign up to set email alerts
|

Continuing Robot Skill Learning after Demonstration with Human Feedback

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Under the social distancing circumstances, people can avoid infections caused by close contact through teleoperate robots to execute tasks. It has been shown that robots can learn by imitating human operators or other robots, which is often referred to as learning by imitation or programming by demonstration to avoid intricate code programming [1]- [2]. Some studies have attempted to solve humanoid robot imitation problems, but there are still have several that need to be solved [3].…”
Section: Introductionmentioning
confidence: 99%
“…Under the social distancing circumstances, people can avoid infections caused by close contact through teleoperate robots to execute tasks. It has been shown that robots can learn by imitating human operators or other robots, which is often referred to as learning by imitation or programming by demonstration to avoid intricate code programming [1]- [2]. Some studies have attempted to solve humanoid robot imitation problems, but there are still have several that need to be solved [3].…”
Section: Introductionmentioning
confidence: 99%